Cold filamentary accretion and the formation of metal-poor globular clusters and Halo stars - Mandelker, Nir; Dokkum, Pieter G. van; Brodie, Jean P.; Bosch, Frank C. van den; Ceverino, Daniel (The astrophysical journal, 2018)
We propose that cold filamentary accretion in massive galaxies at high redshifts can lead to the formation of star-forming clumps in the halos of these galaxies without dark matter substructure. In certain cases, these clumps can be the birthplaces of metal-poor globular clusters (MP GCs). Using cosmological simulations, we show that narrow streams of dense gas feeding massive galaxies from the cosmic web can fragment, producing star-forming clumps. We then derive an analytical model for the properties of streams as a function of halo mass and redshift, and assess when these are gravitationally unstable, when this can lead to collapse and star formation in the halo, and when it may result in the formation of MP GCs. For stream metallicities , this is likely to occur at . At , the collapsing clouds have masses of , and the average stream pressure is . The conditions for GC formation are met in the extremely turbulent “eyewall” at , where counter-rotating streams can collide, driving very large densities. Our scenario can account for the observed kinematics and spatial distribution of MP GCs, the correlation between their mass and metallicity, and the mass ratio between the GC system and the host halo. For MW-mass halos, we infer that of MP GCs could have formed in this way, with the remainder likely accreted in mergers. Our predictions for GC formation along circumgalactic filaments at high redshift are testable with JWST.
Gesehen am 10.10.2019